NGREMBEL ASRI MOBILE BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - The development of today's technology has a huge influence to the world of information technology and telecommunications . The emergence of a variety of applications provide options in improving the performance of a job , either besifat desktop based, web BaseB to present the emergence of new applications that run on the mobile Android Platform system . Ngrembel Asri is a fishing attractions and restaurants in Semarang is addressed at Jl . Manyaran Gunungpati KM 10 Semarang , Central Java , therein presenting a wide range of facilities such as games , outbound , fishing , restaurant , swimming pool etc. . Little information was difficult for visitors to find directions to the location or nets Ngrembel Asri , so the application needs to hold all the information about the location , food and beverage menus , these kinds of games , facilities available , the list price and reservations , the purpose of designing applications Android -Based Mobile Ngrembel Asri is to facilitate the user to find the information and location of Ngrembel Asri . This application is built to allow users to find information more quickly and efficiently . This application will be implemented to keep track of today's mobile technology platforms , namely the android platform .Keywords : Mobile Applications , Ngrembel Asri , Android .